Haematological Changes in Patients with Pulmonary and Extrapulmonary Tuberculosis: A Cross-sectional Study - Chirag H Chakravarti; Rushikesh R Yadav; Arti D Shah; Bhavesh M Patel; Duddilla Sai Venkata Vishwanath Gupta (Journal of Clinical and Diagnostic Research)
Introduction: Mycobacterium tuberculosis interacts with the body’s immune system, resulting in the migration of neutrophils, followed by monocytes and macrophages, which activate T cells and eventually lead to clinical symptoms. Anaemia and other thrombocytic and leucocytic parameters are the most common haematological alterations analysed in tuberculosis. Both Pulmonary Tuberculosis (PTB) and Extrapulmonary Tuberculosis (EPTB) are associated with changes in haematological parameters, which are typically reversible with antituberculosis medication. Aim: This study aims to analyse the haematological changes observed in patients with pulmonary and extrapulmonary tuberculosis visiting a tertiary care hospital in Vadodara, Gujarat. Materials and Methods: A cross-sectional study was conducted from April 2023 to January 2024 in the Department of Respiratory Medicine at Sumandeep Vidyapeeth/Dhiraj Hospital, Vadodara, Gujarat, India. Haematological examinations and comparisons were performed on all 100 newly diagnosed pulmonary and extrapulmonary tuberculosis patients. Data were analysed using the Chi-square test. Results: In the present study, out of a total of 100 patients, 64 were males and 36 were females, with a mean age of 38.55±5.8 years. Anaemia was found in 68.96% of pulmonary tuberculosis patients and in 47.61% of extrapulmonary tuberculosis patients. The prevalence of leucocytosis was higher in pulmonary tuberculosis (82.75%) compared to extrapulmonary tuberculosis (28.57%). Thrombocytosis was more prevalent in extrapulmonary TB (80.95%) than in pulmonary TB (50%). Thrombocytopenia was more common in pulmonary TB (24.13%) than in extrapulmonary TB (21.4%). Conclusion: This study confirms that both pulmonary and extrapulmonary tuberculosis disrupt haematological parameters, highlighting the systemic effects of the disease on various organ systems. These markers are useful for assessing illness severity, monitoring treatment response, and guiding patient management.